Optimization of Phenol Levels from Phycoerythrin of Gracilaria verrucosa with Freeze Thaw using Response Surface Methodology - Maksum, Ali; Purbowati, ike Sitoresmi Mulyo; wijonarko, gunawan; anggriawan, rian (Journal of Agricultural and Biosystem Engineering Research, 2022)
Gracilaria verrucosa is a one of the seaweeds with a red pigment in the form of phycoerythrin. Phycoerythrin pigment contains phenol which is an antioxidant. The pigment can be obtained by extraction. One of the extraction methods that can be done is freeze thaw. This study uses the Response Surface Methodology to obtain the optimum sample. The purpose of this study was to determine the optimization model, the optimum point and the phenol content of the phycoerythrin Gracilaria verrucosa using the freeze thaw using Response Surface Methodology. Extraction of phycoerythrin pigment was carried out using the freeze thaw with a factor of freeze time, thawing time and solvent ratio, then the phenol content test was carried out. The results obtained are that the mathematical model used for optimization is the quadratic method with the equation y = 148.71 – 3.47(A) + 20.94(B) + 32.36(C) + 10.94(AB) + 9 .90(AC) + 6.25 (BC) + 6.52(A2) – 15.57(B2) + 30.46(C2). The optimum response obtained is the freeze duration 121,964 minutes; thawing duration 144,281 minutes; and the solvent ratio is 62.556%, and the phenol content obtained is 163.742 g GAE/g.